THE INFLUENCE OF INFLATION ON THE UNEMPLOYMENT RATE OPEN IN INDONESIA - Parlagutan Lubis, M.Yusuf; Sastri Mara, Dilla; Samosir, Wilson; Sumule, Arsiaty; Delfahedah, Yulia (Universitas Efarina, 2022)
The purpose of this research is to find out.The Influence of Inflation on the Open Unemployment Rate in Indonesia based on the research results it can be seen thatobtained tcount value of 0.992 With α = 5%, ttable (5%; 36-k = 35) obtained ttable value of 2.030 From this description it can be seen that tcount (0.992) < ttable (2.030), and its significance value is 0.328 > 0 .05, it can be concluded that the first hypothesis is rejected, meaningInflation Rate(X) has no significant effectto the Open Unemployment Rate (Y). In other words, the inflation rate has no significant effect on the unemployment rate in Indonesia.